Matriz, capelas e desobrigas: um olhar sobre a cristianização do espaço da Freguesia do Seridó (1788-1838) - Medeiros, Isac Alisson Viana de (2020)
It proposes a study about the territory of the Freguesia da Gloriosa Senhora de Santa Ana do Seridó (1788 to 1838), from the religious temples - headquarters and chapels - built in the area in question. According to Marcelo Lopes Souza, the territory is understood by a space defined and delimited by and from power relations. In this sense, it addresses the territorialization of the freguesia, understanding the Catholic Church as a modeling agent of space. Christian doctrine is considered to be established as a set of practices that have the function of controlling the territory and people over their own guidelines and interests, based on strategies that aim to maintain the existence and legitimize the faith, as well as the its reproduction throughout history. The construction of religious temples was one of those strategies that acted with the intention of modeling the space conquered with Christian characteristics that would help to maintain control and possession of the lands under the power of the Portuguese Crown in partnership with the Catholic Church. In this sense, the acts of release also acted - a process by which the priests moved around the territory performing Christian rites -, from the religious assistance given to the population furthest from the centers of the parish, the priests exercised at the same time some control and organization of the territory, avoiding that his “flock” deviated from Christian norms. The concept of appropriate spatial Christianization by Cláudia Damasceno Fonseca, on the other hand, is essential to discuss the spatiality of religious buildings in the parish of Seridó, as well as their contribution to the control and maintenance of the power of the Catholic religion in the territory. In this sense, the study starts from the assumption that a part of the Church's conquest passed through the Christianization of the space to be dominated, giving him characteristics specific to his religion, in order to mark his domain and establish a system for maintaining his faith among the population that resided there. Methodologically, part of a historiographical review; selection, collection and quantitative and qualitative analysis of freguesia sources - baptism, marriage and death books, which go from 1788 to 1838 and together add up to a total of 4,024 records - to establish the profile of the ceremonies that took place in the religious temples of the parish, as well as the production of the trajectory of the historical process of its emergence and contribution to the production of the territory. It was concluded that the Freguesia do Seridó was constituted as a Christian territory, having in the figure of the religious temples an element of great relevance for this process, since they acted as centers of spreading the Catholic religion - symbol of the success of the Portuguese conquest in the sertões - if we understand that its construction was directly linked to the process of populating the lands of the Sertão do Seridó, with the establishment of the villages and the parish headquarters being closely linked to the construction of these buildings in the area to be populated.